PENDEKATAN BIMBINGAN DAN KONSELING KELOMPOK DALAM MENINGKATKAN PERKEMBANGAN SOSIAL-EMOSIONAL SISWA: A SYSTEMATIC LITERATURE REVIEW - Sofyan Setiawan; Andi Nurfadillah Matta (Fakultas Dakwah dan Ushuluddin Universitas Ibrahimy, 2026)
This study aims to examine the application of the group guidance and counseling approach in improving students' social-emotional development through the Systematic Literature Review (SLR) method. The study was conducted by searching scientific articles from the Scopus, SpringerLink, and Google Scholar databases for the period 2021–2025. The literature selection process used the PRISMA flow, starting from 157 identified articles to produce 11 articles that met the inclusion criteria and were analyzed thematically. The results of the study indicate that the group guidance and counseling approach is implemented in a structured and systematic manner through the stages of needs identification, service planning, group formation, intervention implementation, evaluation, and follow-up. Various techniques used include social emotional learning, role-playing, cinematherapy, and game media. The research findings show that group guidance and counseling services are effective in improving emotional regulation, emotional intelligence, empathy, social skills, peer relationships, self-awareness, and responsible decision-making, while also helping to reduce certain psychological and behavioral barriers. Thus, group guidance and counseling can be seen as an effective, adaptive, and strategic approach in supporting students' social-emotional development in educational environments.